FRI0701-HPR EFFICACY OF INTERMITTENT AEROBIC EXERCISE ON SLEEP EFFICIENCY IN PATIENTS WITH RHEUMATOID ARTHRITIS. A RANDOMIZED CONTROLLED TRIAL. (June 2019) - Løppenthin, Katrine; Midtgaard, Julie; Esbensen, Bente Appel; Ǿstergaard, Mikkel; Christensen, Jesper Frank; Thomsen, Tanja; Tolver, Anders; Jennum, Poul
Abstract : Background: Insomnia is seen in >60% of patients with rheumatoid arthritis (RA). While cross-sectional studies have shown a positive association between regular physical activity and good sleep, there is a lack of knowledge on the effect of physical activity on insomnia in patients with RA. Objectives: To examine the efficacy of intermittent aerobic exercise on sleep efficiency as well as the effect on fatigue and depressive symptoms. Methods: 38 patients with RA were randomly assigned to either intermittent aerobic exercise training; 3 session/week for 6 weeks; intervention group (n=17) or usual care (controls group n=21). The primary outcome was change in polysomnography (PSG) assessed sleep efficiency while secondary outcomes included sleep (Pittsburgh Sleep Quality Index), fatigue (Bristol Rheumatoid Arthritis Fatigue Multi-Dimensional Questionnaire) and depression (The Center for Epidemiological Studies-Depression). Results: Sleep efficiency improved significantly in the intervention group from baseline 0.84 (95% CI 0.80-0.87) to end of the intervention 0.88 (95% CI 0.84-0.92) p=0.03, while for the control group the mean change was not significant. No between-group difference in change was observed. Fatigue was significantly reduced in the intervention group compared to the control group -16.0 (95%CI -25.1 - -7, 04), including physical fatigue -4.99 (95%CI -7.25 - -2.74), cognitive fatigue -2.43 (95%CI -4.22 - -0.63) and living with fatigue -2.50 (95%CI -4.45- -0.54). Conclusion: An intermittent aerobic exercise intervention presented no statistically significant effect on sleep efficiency in patients with RA compared with usual care. However, significant between-group differences were seen in subjectively reported fatigue including physical fatigue and cognitive fatigue and on depressive symptoms. References: [1] Loppenthin K, Esbensen BA, Jennum P, et al. Effect of intermittent aerobic exercise on sleep quality and sleep disturbances in patients with rheumatoid arthritis - design of a randomized controlled trial. BMC musculoskeletal disorders2014 Disclosure of Interests: Katrine Løppenthin: None declared, Julie Midtgaard: None declared, Bente Appel Esbensen Speakers bureau: For Pfizer, Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Jesper Frank Christensen: None declared, Tanja Thomsen: None declared, Anders Tolver: None declared, Poul Jennum: None declared